Studi Eksperimen Pengaruh Ekstrak Kulit Nanas terhadap Laju Pertumbuhan Mikrofouling - Wazirotus Sakinah; Achmad Ilham Dwi Prasetyo; Nugroho Jarot Dwi Ardiansyah; Rudianto Rudianto; Akhmad Ganefo; Yanuar Nurdiansyah (Program Studi Teknik Kelautan Universitas Abdurachman Saleh Situbondo, 2023)
Biofouling often sticks to the ship's hull, even to the propeller parts and pipes that are submerged in water. The existence of this biofouling has an impact on the ship's performance, reducing it and requiring more fuel, which ultimately contributes significantly to increased costs. Microfouling is one of the stages of biofouling growth that appears in a matter of days to weeks with a size of up to 1 mm which can be characterized by the appearance of a slippery layer on the surface of the specimen. Until now, many antifouling paints, as a means of preventing the occurrence of biofouling, still contain TBT, which has serious side effects as a chemical pollutant. Pineapple peel is a waste that is often found in Indonesia and contains bromelain and tannin which are anti-bacterial. The appearance of bacteria is the first phase in the growth of biofouling which is usually called biofilm, so it is hoped that pineapple peel extract will be able to prevent the emergence of biofilm. To determine the effectiveness of pineapple peel extract, this experimental study was carried out. The method used was a Randomized Block Design on ASTM 36 steel plate which is a certified ship material with 3 variations and 1 control of specimen as follows, 3 specimens as controls, 3 specimens with a ratio of 30% pineapple peel extract, 3 specimens with a ratio of pineapple peel extract. 50%, and 3 specimens with a pineapple peel extract ratio of 70%. Immersion for 7 weeks was carried out at Boom Beach, Banyuwangi by calculating the DGR (Daily Growth Rate) once a week. The DGR results obtained were respectively 0.095 g/day at an extract ratio of 30%, 0.0727 g/day at an extract ratio of 50%, and 0.0730 g/day at an extract ratio of 70%.